Nitrate Content in Groundwater and Assessment of Potential Risks for Health of the Rural Population in Novograd-Volyn Raion Zhytomyr District - Valerko , R. A. (Visnyk of V. N. Karazin Kharkiv National University. Series Еcоlogy, 2021)
Purpose. Investigate the content of nitrates in drinking water from sources of decentralized water supply in rural areas of the newly enlarged Novograd-Volynsky district of Zhytomyr region and assess the potential risks for different categories of the local population from constant consumption of water with high nitrate content. Methods. Field, laboratory-analytical, statistical. Results. It was found that the most polluted is the drinking water of private wells located in the former Yemilchyn district, which is now a part of the Novograd-Volyn district, where all samples were found to exceed the concentration of nitrates, and their average content was 99.04 mg/dm3. In general, 57.5% of the selected drinking water samples of the enlarged district were found to exceed the level of nitrates, and their average concentration in the whole district was 67.86 mg/dm3. The largest excess of nitrates in water in 7.9 times was found in a private well in the village of Kamyanka, Barashivka territorial community. It is proved that the risk index due to drinking water consumption for children is 1.8 times higher than for adults. The risk at the maximum content of nitrates for children is set at a high level, and for adults - at an average, and at an average content of nitrates in drinking water, the risk for children is set at a medium level, and for adults - at a low level. Conclusions. It has been shown that the overall risk of nitrate intake in both routes is approximately equal to the health risk due to drinking water consumption. In the overall risk, the share of non-carcinogenic risk due to drinking water consumption was 99.5%, which is much higher than in contact with the skin. This indicates that nitrates from groundwater enter the human body mainly with drinking water, so it is necessary to constantly monitor their content in drinking water. verage content of nitrates